A Study of Mullā Ṣadrā’s Method of Use of Various Sources and Explanations that Can Be Proposed about It - Saeed Anvari; Maryam Mahdavi Mazdeh (آموزه‌‌های فلسفه اسلامي, 2021)
In this article, by categorizing the methods of referring Mullā Ṣadrā, evidence of the similarity of his statements with the works of others has been shown, which has led to the accusation of piracy (plagiarism). An attempt has been made in this research to explain the causes of this event in his works. For this purpose, with the analytical-historical method, seventeen different explanations about the reason for adapting Mullā Ṣadrā from the expressions of others have been proposed and evaluated and it has been shown that some of these explanations are not acceptable. Acceptable explanations were then divided into two categories of specific and general explanations. Specific explanations include: trying to write a comprehensive book, transmitting Sunni theories to Shiite books, and using other people’s contents to consecrate, guarantee, and adapt popular phrases. General explanations are also: the prevalence of unsourced quotations in philosophical texts, the instrumental view of theoretical wisdom, the need to maintain the didactic aspect in the expression of topics, the confirmation of one’s own opinions by quoting others, and the avoidance of phrase reprocessing. Accordingly, not all expressions in Mullā Ṣadrā’s works are necessarily his own, and researchers must be more careful in their attribution.